2019
DOI: 10.18391/req.v20i1.4856
|View full text |Cite
|
Sign up to set email alerts
|

Desenvolvimento Social E Econômico: Crescimento Populacional E Capital Social No Município De Caraguatatuba/Sp

Abstract: O município de Caraguatatuba passou por um forte processo de urbanização, acompanhado de acentuado crescimento demográfico nas últimas décadas. O objetivo do artigo foi demonstrar como o rápido crescimento populacional no munícipio, derivado de uma forte migração nas últimas décadas, dificultou a formação das condições necessárias à constituição de capital social. O método consistiu na comparação entre dados secundários e os resultados produzidos mediante a aplicação de questionário para a caracterização do ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
0
0
Order By: Relevance
“…It is implied that employment generation is high, since input traders are considered essential agents of the production chain and need to necessarily obtain manpower to address customer requirements. Santos et al (2019) confirmed the scope of formal jobs in the agricultural sector, taking as an example the city of Caraguatatuba (SP), where in the percentage of workers employed in commerce and service were 40.31% and 45.85%, respectively.…”
Section: Resultsmentioning
confidence: 73%
See 1 more Smart Citation
“…It is implied that employment generation is high, since input traders are considered essential agents of the production chain and need to necessarily obtain manpower to address customer requirements. Santos et al (2019) confirmed the scope of formal jobs in the agricultural sector, taking as an example the city of Caraguatatuba (SP), where in the percentage of workers employed in commerce and service were 40.31% and 45.85%, respectively.…”
Section: Resultsmentioning
confidence: 73%
“…Social capital is employed to help understand how relationships and sociability are established in a territory. Its characterization helps understand better the relationship between citizens and their collective organization (Santos, Vieira & Santos, 2019). Willers et al (2008) highlighted that the establishment of social networks and productive groups (cooperatives and associations) provided better survival conditions in a competitive scenario.…”
Section: Resultsmentioning
confidence: 99%